Pola Pendidikan Life Skill Melalui Fun Friday Class Di Pesantren Ngalah - muhammad Nurhadi (Universitas Yudharta Pasuruan, 2021)
This research aims to reveal the pattern of life skill education through Fun Friday Class in Pesantren Ngalah Pasuruan. The data source of this study is divided into two, namely: primary data; Asrama activities, Asrama Work Program, life skills activities in the dormitory. Secondary data includes; Asrama Profile, Admin Profile, and Student Profile. Data collection techniques using (1) Participant Observation, (2) In-depth Interviews, and (3) Documentation Studies. The data is analyzed by stages (1) Data Reduction, (2) Data Presentation, and (3) Verification (Drawing Conclusions). Validity of data using data triangulation method, source triangulation and triangulation technique. Pattern of life skill education a. personal skill aspect, polar qiroatul b. social aspect of skill, shalawat c. academic aspect of skill, jawabul masail and atlas walisongo and d. vocational aspects of skill, al-banjari, speech, and qiroah. supporting elements of life skill education through fun friday class, : Development of insights, creativity and talents of students that have a positive impact on the development of life skills education santri. The material used in learning is always repeated to review the previous material. Train public speaking students so that students are able to implement the potential of students in the community. Elements of life skill education inhibition (a) lack of time used in the fun friday class program so that learning is less than maximum, (2) lack of interest in students in joining the fun friday class program because the program is a santri obligation that must be followed so that students follow the program only as a deed of obligation only